AN ANALYSIS OF PSYCHOSOCIAL CONDITIONS A CASE STUDY AT BPPK (BADAN PENDIDIKAN DAN PELATIHAN KEUANGAN-FINANCE OF EDUCATION & TRAINING AGENCY) â MINISTRY OF FINANCE OF THE REPUBLIC OF INDONESIA - Dedy Nurtanto, Taufan
Every year, BPPK, an agency of the Ministry of Finance, has an organisational performance indicator (referred to KPI, key performance indicator). In order to achieve these KPIs, BPPK needs employees and creates favourable psychosocial environments. The purpose of this study is to describe these psychological conditions. To determine what kind of psychosocial circumstances at BPPK have been successful in achieving the annual organisational KPI. The COPSOQ III questionnaire, a tool that has been tested and validated both worldwide and nationally in Indonesia, was used to collect data for psychosocial study. An online questionnaire was used to conduct this 147-item questionnaire, and 304 individuals from different BPPK organisations finally participated. According to the results of the COPSOQ III questionnaire, the psychosocial environment of BPPK was generally in favourable condition. These findings came from a descriptive analysis of variability (standard deviation, skewness, and kurtosis) and central tendency (mean, mode, and median). Additionally, each psychosocial dimension's proportion of respondents' conditions were classified according to their condition. Although the psychosocial dimensions are generally in favourable condition, BPPK should be concerned about 14 dimensions scattered over 7 domains. Aside from job satisfaction, which does not include respondents in the very poor category, all dimensions distribute respondents throughout all categories. These findings indicate that, even though the annual organisational KPI is fulfilled, BPPK still has to be cognizant of the psychosocial state of its employees. To lower the proportion of employees with very poor psychosocial conditions and to move all psychosocial dimensions into the very good and good categories, managerial strategic policies and initiatives are required.